Implementation of the Water Park Concept of Traditional Balinese Architecture in Improvement Comfort Thermal at Captain Mudita Bangli Park - I Wayan Wirya Sastrawan; I Gede Surya Darmawan; I Putu Hartawan (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
Comfort thermal is absolute thing for body human, therefore human always try conditioning environment to achieve comfort thermal for his body. Outdoor space is one a place where humans operate. Object in This research is environment planned construction with apply element architecture external supported by architectural concepts traditional Balinese. See condition that, there is opportunity and important to learn characteristics comfort thermal water park. This research aims to find out factor comfort thermal and outdoor factors in the Field Captain Mudita Bangli. Field Captain Mudita Bangli chosen as location study Because own characteristic typical separately, as well role very important as support life people in Bangli. The purpose of This research is to find out spread condition thermal, knowing big influence factor external to condition thermal and the influence of water park spatial models according to Balinese traditional concepts. architecture comfort thermal. The results of this research can be become base for architects to build and design water park that can operate optimally. In this research, method comparison and simulation used to visualize condition comfort thermal on the subject research. From the results of this simulation, it can be used to find out influence factor external and architectural concept traditional Balinese towards comfort thermal object research.